Drug–drug interactions in nursing home residents: analysis from the COME-ON trial. - Lion, Simon; Evrard, Perrine; Foulon, Veerle; Spinewine, Anne (Age & Ageing, 2023)
Background as a result of the high prevalence of polypharmacy in nursing homes (NHs), nursing home residents (NHRs) are exposed to numerous drug–drug interactions (DDIs) that can lead to adverse drug effects, and increased morbidity and mortality. Objectives to evaluate (i) the prevalence of DDIs among NHRs and its evolution over time, and (ii) factors associated with a favourable evolution. Design posthoc analysis of the COME-ON study, a cluster-randomised controlled trial aiming at reducing potentially inappropriate prescriptions in NHs, through the implementation of a complex intervention. Setting and subjects 901 NHRs from 54 Belgian NHs. Methods DDIs were identified using a validated list of 66 potentially clinically relevant DDIs in older adults. We defined a favourable evolution at 15 months as the resolution of at least one DDI present at baseline, without the introduction of any new DDI. Factors associated with a favourable evolution were analysed using multivariable logistic regression. Results at baseline, 475 NHRs (52.7%) were exposed to at least 1 DDI and 225 NHRs (25.0%) to more than one DDI. Most common DDI was 'Concomitant use of at least three central nervous system active drugs'. At 15 months, we observed a 6.3% absolute decrease in DDI prevalence in intervention group, and a 1.0% absolute increase in control group. The intervention, older age and private NH ownership were significantly associated with a favourable DDI evolution. Conclusion a high prevalence of DDI in Belgian NHs was observed, but the COME-ON intervention was associated with a favourable evolution over time.